PENGARUH KETERTARIKAN PRODUK MERK GLOBAL DAN MERK LOKAL TERHADAP KEPUTUSAN PEMBELIAN: Studi Kasus Mahasiswa UINSU - Pasaribu, Aisyah Fitri; Suhairi, Suhairi; Wiranti, Wiranti; Kurniawan, Alfarizi (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to determine the effect of interest in global brand products and local brands in purchasing decisions for UINSU students. This study uses a descriptive qualitative research method which aims to find out the reality of the field in depth and specific and the elaboration is carried out in an in-depth and open manner to provide data proving a phenomenon or event whose data processing is carried out by elaboration. The results of this study are the factors that determine purchases in local products and global products, namely quality, price, brand, and quantity